Survei Penilaian Integritas: Alternatif Pengukuran Kinerja Pemberantasan Korupsi - Susilo, Wahyu Dewantara; Angraeni, Sari; Partohap, Timotius Hendrik (Komisi Pemberantasan Korupsi, 2019)
The Integrity Assessment (IA) is a tool developed by Directorate of Research and Development to assess the risk of corruption and measure the milestones of corruption prevention effort in Ministries/Institutions/Local Government. The IA is a measurement tool that combine experience and perception from the perspective of public officials, the users of public services, as well as experts in assessing the integrity of one institution. In 2018, the average integrity index from 6 Ministries/Institutions and 20 Provincial Government is 68,75 from the scale of 1 to 100. Conflict of interests, bribery/gratutity in both public services and management of human resources, and whistleblower protection are still the main issues of integrity in the Ministries/Institutions/Local Governments.